Implementation of Portfolio Assessment on Tahsin Kitabah Teaching at Al-Hidayah Karangploso Boarding School - Fawzani, Nurul; Zahro, Fatimatuz; Fitra , Muh. Naufal; Prayetno, Eko (Al-Lisan: Jurnal Bahasa, 2024)
Differences in writing abilities between students encourage teachers to design or have special assessment tools to evaluate the development of their abilities. Al-Hidayah Islamic Boarding School applies portfolio assessment as an assessment instrument in the Tahsin kitabah subject. So, this research aims to determine the form of portfolio assessment used in Tahsin kitabah lessons, the steps for portfolio assessment, and their impact on tahsin kitabah learning at the Al-Hidayah Karangploso cottage. This research is qualitative descriptive research, where the data collection process is done through interviews and documentation. The data analysis goes through the stages of data collection, data reduction, data presentation, and conclusion. The results of this research indicate that the form of portfolio assessment used in the Tahsin kitabah subject at the Al-Hidayah Islamic Boarding School is an evaluative portfolio because it emphasizes assessment and reflection carried out in a formative and summative manner. The portfolio assessment steps in the Tahsin kitabah subject consist of three main stages. The preparation stage includes identifying learning objectives, explaining them to students, and clarifying portfolio components. The Implementation Stage involves teacher encouragement, discussion of learning progress, and continuous feedback. At the Assessment Stage, criteria are determined with students, applied consistently, and emphasize self-assessment. The impact includes teachers' in-depth understanding of students' writing abilities, increased motivation, self-confidence, and active learning participation. This shows that the implementation of portfolio assessment at the Al-Hidayah Islamic Boarding School has proven to be effective in achieving Tahsin kitabah’s learning objectives.